2009
DOI: 10.1517/14656560903140525
|View full text |Cite
|
Sign up to set email alerts
|

The economic implications of generic substitution of antiepileptic drugs: a review of recent evidence

Abstract: Current literature suggests statistically higher overall healthcare costs during periods of generic AED use than during periods when branded AED are used, consistently demonstrated across different countries (Canada and the USA) and in both stable and unstable epilepsy patients, with more pronounced cost increases in patients receiving multiple generic versions. Brand-to-generic substitutions of AEDs do not necessarily reduce overall healthcare costs and may even increase them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 39 publications
1
16
0
2
Order By: Relevance
“…The actual savings generated by a compulsory switch from Lamictal to generic lamotrigine in Ontario, Canada, were much smaller than expected (Duh et al, 2007). In a recent review, Duh et al (2009) concluded that overall health care costs were higher during periods of generic anticonvulsants use than during periods of brand name use in Canada and the USA. Layton and Barbeau (2004) calculated the potential cost savings of switching patients from Clozaril to generic clozapine in Canada based on the incidence of relapses associated with the switch.…”
Section: Discussionmentioning
confidence: 94%
“…The actual savings generated by a compulsory switch from Lamictal to generic lamotrigine in Ontario, Canada, were much smaller than expected (Duh et al, 2007). In a recent review, Duh et al (2009) concluded that overall health care costs were higher during periods of generic anticonvulsants use than during periods of brand name use in Canada and the USA. Layton and Barbeau (2004) calculated the potential cost savings of switching patients from Clozaril to generic clozapine in Canada based on the incidence of relapses associated with the switch.…”
Section: Discussionmentioning
confidence: 94%
“…Physicians and pharmacists agree that sometimes, there could a genuine reason to use branded medications but this should be as situations demand. 25,26 in their report agreed that the use of generic medications does not always guarantee cost savings for certain diseases, even though clinical outcome might be similar to their branded counterparts. On the other hand, community Pharmacies have been known to consider gain over affordability when dispensing medications to patients.…”
Section: Discussionmentioning
confidence: 99%
“…have concluded that there really does not seem to be any conclusive association between generic substitution and either loss of seizure control or new, treatment-emergent adverse effects (2), although there clearly is a suggestion that when generic substitution occurs, expenditures of resources goes up (3,4).…”
Section: Generic Antiepileptic Drugs: How Good Is Close Enough?mentioning
confidence: 99%